Towards a system of lifelong education : some practical considerations - Cropley, A. J. (Advances in lifelong education, 1980)
Towards a System of Lifelong Education: Some Practical Considerations focuses on the need to create a sound system of lifelong education, taking into consideration the processes, conditions, and factors involved.